2008
DOI: 10.1007/s10545-007-0798-1
|View full text |Cite
|
Sign up to set email alerts
|

Methylmalonate inhibits succinate‐supported oxygen consumption by interfering with mitochondrial succinate uptake

Abstract: The effect of methylmalonate (MMA) on mitochondrial succinate oxidation has received great attention since it could present an important role in energy metabolism impairment in methylmalonic acidaemia. In the present work, we show that while millimolar concentrations of MMA inhibit succinate-supported oxygen consumption by isolated rat brain or muscle mitochondria, there is no effect when either a pool of NADH-linked substrates or N,N,N',N'-tetramethyl-p-phenylendiamine (TMPD)/ascorbate were used as electron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…45 Methylmalonate has been shown to impair succinate oxidation in isolated muscle mitochondria. 46 Maleate can sequester mitochondrial CoA and thus inhibit oxidation of other CoA-dependent substrates. 47 However, it is unclear how plasma levels of these metabolites reflect their intracellular concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…45 Methylmalonate has been shown to impair succinate oxidation in isolated muscle mitochondria. 46 Maleate can sequester mitochondrial CoA and thus inhibit oxidation of other CoA-dependent substrates. 47 However, it is unclear how plasma levels of these metabolites reflect their intracellular concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the precise mechanisms underlying complication development remain unclear, even if a role of toxic metabolites is probable (21). Apart from metabolic enzyme inhibition, MA was recently shown to inhibit the mitochondrial dicarboxylate carrier in vitro (22) suggesting that it may alter the transport of various dicarboxylic acids into mitochondria including TCA cycle intermediates (23). This mechanism may thus result in further energy metabolism deficiency and contribute to the global OXPHOS deficiency in the patients' tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Current work indicated clearly that Wistar rats produced higher levels of methylmalonic and succinic acid in pairs than SD rats. Mirandola et al's (2008) work demonstrated that methylmalonic acid inhibited the oxidation of succinic acid in mitochondria, and hence higher concentrations of succinic acid were excreted together with methylmalonic acid in the urines of fasting Wistar rats compared to the fasting SD rats. Additionally, it was interesting to find that ethylmalonic and methylsuccinic acids were both significantly higher in SD rats rather than Wistar rats in the fasting condition, suggesting that the SD rats probably produced higher levels of metabolites relating to ethylmalonic encephalopathy than Wistar rats (Nowaczyk et al 1998).…”
Section: Metabolomic Variations Between Sd and Wistar Rats In Fastingmentioning
confidence: 99%